Loss of multilevel 3D genome organization during breast cancer progression - Rossini, Roberto; Oshaghi, Saleh; Nekrasov, Maxim; Bellanger, Aurélie; Domaschenz, Renae; Dijkwel, Yasmin; Abdelhalim, Mohamed; Agrawal, Rahul; Ledsaak, Marit; Collas, Philippe; Eskeland, Ragnhild; Tremethick, David; et al. (Genome Research, 2025)
Breast cancer entails intricate alterations in genome organization and expression. However, how three-dimensional (3D) chromatin structure changes in the progression from a normal to a breast cancer malignant state remains unknown. To address this, we conducted an analysis combining Hi-C data with lamina-associated domains (LADs), epigenomic marks, and gene expression in an in vitro model of breast cancer progression. Our results reveal that while the fundamental properties of topologically associating domains (TADs) are overall maintained, significant changes occur in the organization of compartments and subcompartments. These changes are closely correlated with alterations in the expression of oncogenic genes. We also observe a restructuring of TAD-TAD interactions, coinciding with a loss of spatial compartmentalization and radial positioning of the 3D genome. Notably, we identify a previously unrecognized interchromosomal insertion event, wherein a locus on Chromosome 8 housing the MYC oncogene is inserted into a highly active subcompartment on Chromosome 10. This insertion is accompanied by the formation of de novo enhancer contacts and activation of MYC, illustrating how structural genomic variants can alter the 3D genome during oncogenesis. In summary, our findings provide evidence for the loss of genome organization at multiple scales during breast cancer progression revealing novel relationships between genome 3D structure and oncogenic processes.